(untitled) (Foro de Educacion, 2026)
During last few years, higher education is going through rapid transformation because of which professional and ethical values have become critical to shape personalities of students. Professional and ethical values are important tools for regulatory behavior. Therefore, this research aimed to explore the level to which professional and ethical code of conduct contributes to provide guidelines of professional and academic behavior for students at King Fahad University. This study is also intended to find out differences on the basis of specialization, gender and academic level among students. Data was collected from the students at King Fahad University using questionnaires. Study employed stratified random sampling to reach and collect data from students. The analysis of the study was conducted through SPSS. The result of the study indicates that awareness of professional and ethical code has overall high score. Also, all the domains show the importance of code to guide professional and academic behavior. There was no statistical difference on the basis of academic specialization or gender. Whereas, a significant difference was reported on the basis of academic level, such as Masters and doctoral students over BS level students. This research shows the importance of strengthening awareness programs at the university level.